Effects of genotype, feed intake and day of measurement on metabolizable variables of roosters - Pérez-Rosas , Eissy; González-Cerón , Fernando; Pro-Martínez , Arturo; Hernández-Blancas, Berenice; Alejos-de la Fuente, José Isidro; Sosa-Montes, Dr. Eliseo (Ecosistemas y Recursos Agropecuarios, 2025)
A study was conducted to determine the interaction of genotype (Creole and Sasso roosters) with feed intake (100 and 50 g day-1) and the effects of evaluation day (1 to 7 consecutive days) on the metabolizable variables (g day-1 or cal day-1, and %): crude protein, ether extract, crude fiber, and energy (also expressed in kcal g-1 of diet). There were a total of 84 observations per variable, 6 Creole, 6 Sasso, 7 days: (6 + 6)×7 under two completely randomized designs, time factor with 7 levels (days of evaluation) and 2×2 factorial arrangement (two genotypes per two levels of intake). On days 1 to 4, almost all variables were similar (p > 0.05) but higher (p < 0.05) than their values on days 5 to 7. Contrary to the other response variables, which did not change or decreased, from day 1 to 4, the metabolizable ether extract increased. Creoles metabolized more protein than Sasso roosters, which metabolized more lipids than Creoles. All response variables were higher when the feed intake was 100 g day-1 than when it was 50 g day-1. In addition to the management of more than 4 days, low feed intake also causes stress, so it is recommended to evaluate energy and metabolizable nutrients in the diets during the first two days after the adaptation and training process, and that the roosters consume at least 100 g of feed per day.
Keywords: Creole; feed consumption; stress; management